Analisis Silika (SiO2) Hasil Kopresipitasi Berbasis Bahan Alam menggunakan Uji XRF dan XRD: Linda Silvia, Mochamad Zainuri - Linda Silvia Linda Silvia; Mochamad Zainuri Mochamad Zainuri (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, LPPM-ITS, 2020)
Synthesis process of silica (SiO2) from Bancar sand has been carried out by coprecipitation method using NaOH. This study tried to obtain high purity silica from the natural resources by analyzing it using the Rietveld method. Experiments are conducted with different training. Study of X-ray Fluorescence (XRF) analysis showed that Bancar sand was used containing a silica composition weight of 81.7%. X-ray Diffraction (XRD) pattern proves that the synthesized SiO2 formed is amorphous silica, but is still a crystal structure, so that amorphous silica has not yet been formed as a whole. SiO2 content obtained showed high purity using the Rietveld method proved by GoF < 4%. By using MAUD software was obtained silica from coprecipitation methods have particle size were 98.4 ± 57.7 nm.